Incidence of Ischemic Stroke in Individuals With and Without Aortic Valve Stenosis: A Danish Retrospective Cohort Study. Issue 5 (May 2020) - Andreasen, Charlotte; Gislason, Gunnar H.; Køber, Lars; Abdulla, Jawdat; Martinsson, Andreas; Smith, J. Gustav; Torp-Pedersen, Christian; Andersson, Charlotte
Abstract : Background and Purpose—: Aortic valve stenosis may lead to atrial and ventricular remodeling, predisposes to atrial fibrillation, and may also be an independent risk factor of ischemic stroke. However, information on stroke rates among persons with aortic valve stenosis are sparse. We aimed to determine the incidence rates and relative risks of ischemic stroke in individuals with diagnosed aortic valve stenosis compared with age- and sex-matched controls. Methods—: All patients with incident aortic valve stenosis aged >18 years (n=79 310) and age- and sex-matched controls were identified using the Danish nationwide registries (1997–2017). Incidence rates per 1000 person-years (PY) and multivariable adjusted hazard ratios with 95% CIs were reported. Results—: In total, 873 373 individuals (median age 77 years, 51.5% men, 9.1% with aortic valve stenosis) were included. Ischemic stroke occurred in 70 205 (8.0%) individuals during 4 880 862 PY of follow-up. Incidence rates of ischemic stroke were 13.3/1000 PY among the controls compared with 30.4/1000 PY in patients with aortic valve stenosis, corresponding to a hazard ratio of 1.31 (95% CI, 1.28–1.34). In all age-groups, the incidence rates and relative risks were significantly increased in patients with aortic valve stenosis compared with controls, but the relative risk was greater for younger individuals (eg, age group, 18–45 years: hazard ratio, 5.94 [95% CI, 4.10–8.36]). In patients with aortic valve stenosis above 65 years of age, the risk of ischemic stroke was markedly lower after aortic valve replacement (30.3 versus 19.6/1000 PY before and after valve replacement). Among people with atrial fibrillation the incidence rate of ischemic stroke was 1.5 times higher when aortic valve stenosis was present (33.0/1000 PY versus 49.9/1000 PY). Conclusions—: People with aortic valve stenosis have a significantly increased risk of ischemic stroke compared with age- and sex-matched controls. Future studies are warranted to explore whether antithrombotic therapy may be beneficial in some individuals. Abstract : Supplemental Digital Content is available in the text.